Molecular basis of V-ATPase inhibition by bafilomycin A1 - Wang, Rong (Nat Commun, 2021)
Pharmacological inhibition of vacuolar-type H(+)-ATPase (V-ATPase) by its specific inhibitor can abrogate tumor metastasis, prevent autophagy, and reduce cellular signaling responses. Bafilomycin A1, a member of macrolide antibiotics and an autophagy inhibitor, serves as a specific and potent V-ATPases inhibitor. Although there are many V-ATPase structures reported, the molecular basis of specific inhibitors on V-ATPase remains unknown. Here, we report the cryo-EM structure of bafilomycin A1 bound intact bovine V-ATPase at an overall resolution of 3.6-Å. The structure reveals six bafilomycin A1 molecules bound to the c-ring. One bafilomycin A1 molecule engages with two c subunits and disrupts the interactions between the c-ring and subunit a, thereby preventing proton translocation. Structural and sequence analyses demonstrate that the bafilomycin A1-binding residues are conserved in yeast and mammalian species and the 7’-hydroxyl group of bafilomycin A1 acts as a unique feature recognized by subunit c.